Metabolomics Study Reveals Inhibition and Metabolic Dysregulation in Staphylococcus aureus Planktonic Cells and Biofilms Induced by Carnosol - Shen, Fengge; Ge, Chunpo; Yuan, Peng (Frontiers in Microbiology, 2020)
Staphylococcus aureus (S. aureus) is a global health threat accompanied by increasing in drug resistance. To combat this challenge, there is an urgent need to find alternative antimicrobial agents against S. aureus. This study investigated the antimicrobial efficacy of carnosol against S. aureus using an in vitro model. The effects of carnosol were determined based on the antimicrobial effects or formation and disruption of biofilms. Finally, metabolomics of S. aureus grown as planktonic cells and biofilms with carnosol treatment were analyzed using gas chromatography-mass spectrometry. The minimum inhibitory concentrations (MICs) of carnosol were 32 to 256 μg/mL against the sixteen tested S. aureus strains. Among the biofilms, we observed a reduction in bacterial motility of the S. aureus, biofilm development and preformed biofilm after carnosol treatment. Moreover, the significantly altered metabolic pathways upon carnosol treatment in S. aureus planktonic cells and biofilms were highly associated with the perturbation of glyoxylate and dicarboxylate metabolism, glycine, serine and threonine metabolism, arginine and proline metabolism, alanine, aspartate and glutamate metabolism, arginine biosynthesis, and aminoacyl-tRNA biosynthesis. In addition, glutathione metabolism, D-glutamine and D-glutamate metabolism were significantly changed in the biofilms. This study establishes the antibacterial and antibiofilm properties of carnosol, and will provide an alternative strategy for overcoming the drug resistance of S. aureus.